Expression Changes of miRNAs in Humans and Animal Models of Amyotrophic Lateral Sclerosis and Their Potential Application for Clinical Diagnosis - Ruili Wang; Liang Chen; Yuning Zhang; Bo Sun; Mengyao Liang (Life, 2024)
Amyotrophic lateral sclerosis (ALS) is a severe motor neuron disease. Current detection methods can only confirm the diagnosis at the onset of the disease, missing the critical window for early treatment. Recent studies using animal models have found that detecting changes in miRNA sites can predict the onset and severity of the disease in its early stages, facilitating early diagnosis and treatment. miRNAs show expression changes in motor neurons that connect the brain, spinal cord, and brain stem, as well as in the skeletal muscle in mouse models of ALS. Clinically, expression changes in some miRNAs in patients align with those in mouse models, such as the upregulation of miR-29b in the brain and the upregulation of miR-206 in the skeletal muscle. This study provides an overview of some miRNA study findings in humans as well as in animal models, including SOD1, FUS, TDP-43, and C9orf72 transgenic mice and wobbler mice, highlighting the potential of miRNAs as diagnostic markers for ALS. miR-21 and miR-206 are aberrantly expressed in both mouse model and patient samples, positioning them as key potential diagnostic markers in ALS. Additionally, miR-29a, miR-29b, miR-181a, and miR-142-3p have shown aberrant expression in both types of samples and show promise as clinical targets for ALS. Finally, miR-1197 and miR-486b-5p have been recently identified as aberrantly expressed miRNAs in mouse models for ALS, although further studies are needed to determine their viability as diagnostic targets.